JunD Regulates Pancreatic β-Cells Function by Altering Lipid Accumulation - Wang, Kexin; Cui, Yixin; Lin, Peng; Yao, Zhina; Sun, Yu (Frontiers in Endocrinology, 2021)
The impairment of pancreatic β-cells function is partly caused by lipotoxicity, which aggravates the development of type 2 diabetes mellitus. Activator Protein 1 member JunD modulates apoptosis and oxidative stress. Recently, it has been found that JunD regulates lipid metabolism in hepatocytes and cardiomyocytes. Here, we studied the role of JunD in pancreatic β-cells. The lipotoxic effects of palmitic acid on INS-1 cells were measured, and JunD small-interfering RNA was used to assess the effect of JunD in regulating lipid metabolism and insulin secretion. The results showed that palmitic acid stimulation induced the overexpression of JunD, impaired glucose-stimulated insulin secretion, and increased intracellular lipid accumulation of β-cells. Moreover, the gene expression involved in lipid metabolism (Scd1, Fabp4, Fas, Cd36, Lpl, and Plin5) was upregulated, while gene expression involved in the pancreatic β-cells function (such as Pdx1, Nkx6.1, Glut2, and Irs-2) was decreased. Gene silencing of JunD reversed the lipotoxic effects induced by PA on β-cells. These results suggested that JunD regulated the function of pancreatic β-cells by altering lipid accumulation.